BIM – AN APPLICATION IN GEOTECHNICAL ENGINEERING - Ivan Vaníček; Jan Pruška; Daniel Jirásko (Acta Polytechnica CTU Proceedings, 2021)
BIM model represents a significant step forward within the frame of the overall process of construction. This new approach goes from the assumption that up to date praxis, which is represented by different sets of 2D or 3D drawings of drawings, technical reports and calculations does not cover all problems of the above mentioned overall process of construction. Basic principles of BIM will be discussed, not only from the view of 3D models of the structure design. The utilization of the BIM model during life time structure expectancy will be stressed - from the initial phase (investigation, design) via the phase of structure execution, maintenance and ending with structure demolition at the end of life time expectancy. Specificity of the geotechnical engineering is in this entire process fundamental, as each construction is in the interaction with ground. 3D model of the ground (geotechnical model) is therefore one of the basic individual parametric elements from which BIM model consist. Ground model is time dependant as geological profile and geotechnical properties are refinement during each phase of ground investigation as well during geotechnical structure construction. Final 3D Ground model together with 3D model of geotechnical structure represents a first significant step of the overall BIM model. In the case of underground or earth structures such output can be primordial element of the BIM model with parametric elements around it. Finally some other possibilities or practical applications are mentioned.